A Quantitative Study on Dream of the Red Chamber: Word-Length Distribution and Authorship Attribution. (10th March 2022) - Yu, Yue; Liu, Wei; Feng, Ying
Abstract : This paper investigates the distribution characteristics of word lengths in the Dream of the Red Chamber (DRC), measured in terms of the number of syllables or characters. The results show that the frequency distribution of words of different lengths in the DRC abides by the extended logarithmic distribution model. A comparison between the first forty, the middle forty, and the last forty chapters shows that the distribution of word lengths in these three parts does not differ significantly, which sheds light on the authorship of the novel.